Morphosyntactic Development and Implicit Learning in Down Syndrome and Related Conditions - Rondal, Jean (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Implicit learning of morphosyntax is attracting much interest in psycholinguistics. Limited data are available from experimental studies in people with cognitive handicap. The paper presents and discusses central aspects of the implicit learning model as it applies to morphosyntactic development in typical children and children and adolescents with cognitive handicap. Several possible reasons for the delays and difficulties usually observed in the latter are examined. Suggestions are made for further research and language intervention in cognitive handicap.